ADVANCES IN REPRODUCTIVE TECHNOLOGIES IN CATTLE: FROM ARTIFICIAL INSEMINATION TO CLONING AVANCES EN BIOTECNOLOÍA REPRODUCTIVA EN BOVINOS: DE LA INSEMINACIÓN ARTIFICIAL A LA CLONACIÓN - Bertolini, L.R; Bertolini, Marcelo (Revista de la Facultad de Medicina Veterinaria y de Zootecnia, 2009)
The urge for the control of reproductive processes in animals has propelled a great gain in knowledge, also setting off the development of four generations of assisted reproductive technologies (AR T) for humans and animals. The use of assisted reproductive techniques has been of great importance in livestock production. In general terms, the main first three generations of ARTs, including 1) artificial insemination (AI) and gamete and embryo freezing, 2) multiple ovulation and embryo transfer (MOET) and 3) in vitro fertilization (IV F) procedures, have matured into successful commercial applications, facilitating the increase in production through genetics, the reduction in generation intervals, the control of diseases, and the cutback in production costs. The fourth generation of AR T encompasses processes that are still more experimental, comprising cloning by nuclear transfer (NT) of embryonic or somatic cells, transgenesis, and stem cell biology. Such technologies are intertwined with one another and with currently available molecular tools, being completely dependent upon the previous generations of technologies. However, many reproductive challenges still hinder maximal livestock reproductive performance, affecting productivity and profitability. It is clear that the application of such technologies as lucrative activities will remain questionable if not associated with other components of animal production, such as animal health, nutrition and adequate animal husbandry practices. El afán por controlar los procesos reproductivos en animales ha llevado a una gran ganancia en conocimiento, impulsando el desarrollo de cuatro tecnologías reproductivas asistidas (AR Ts) para animales y humanos. El uso de AR Ts ha sido de gran importancia en la producción ganadera. En términos generales, las tres principales generaciones de AR T, incluyendo 1) inseminación artificial (AI) y congelación de gametos y embriones, 2) superovulación y transferencia de embriones (MOET) y 3) procedimientos de fertilización in Vitro, han madurado en aplicaciones comerciales exitosas, facilitando el incremento en la producción a través de la genética, reducción del intervalo generacional, control de enfermedades, y reducción de costos de producción. La cuarta generación de AR Ts incluye procesos que aún son muy experimentales, como transferencia de núcleos (NT) de células somáticas, transgénesis, y biología de células madre. Estas tecnologías se intercalan las unas con las otras y con las herramientas moleculares actuales, dependen completamente de las generaciones de tecnologías previas. Sin embargo, hay muchos retos reproductivos que no permiten alcanzar el potencial reproductivo máximo, afectando la productividad y la rentabilidad. Es claro que la aplicación de tales tecnologías como actividades lucrativas se mantendrán cuestionadas si no se asocian a otros componentes de la producción pecuaria, como la salud animal, nutrición, y prácticas de manejo adecuadas.